Dampak Penyelenggaraan KTT Archipelagic and Island States Forum 2023 Terhadap Pariwisata di Bali - Adinatha, Ida Ayu Devina Radharani; Priadarsini, Ni Wayan Rainy (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2025)
This study aims to measure the impact of the 2023 Archipelagic and Island States (AIS) Forum Summit on Bali's tourism sector. Employing a qualitative approach, this research analyzes both primary and secondary data to identify significant changes occurring after the summit. The findings reveal that the AIS Forum made a substantial positive contribution to Bali's economic growth, particularly in the tourism sector. Notably, increased hotel occupancy rates, a surge in tourist arrivals, and local economic growth were observed as direct impacts. Furthermore, the summit played a crucial role in promoting Bali as a sustainable tourism destination, with a particular focus on marine tourism through the concept of the blue economy.